Oral changes and periodontal treatment in a pregnant woman - Falcón-Guerrero, Britto Ebert (2022)
Every woman, when the time has come when her body begins to undergo changes, means that the time has come to be pregnant; without neglecting oral diseases that generate adverse conditions. A narrative review is carried out, until July 2022, when she is in normal conditions, the woman can present certain types of bacteria that can lead to the presence of some type of disease, causing the increase in hormonal levels and nutritional decrease, which continue to create a transitory diminished state. For this reason, the principle of discussing the changes observed in the oral cavity and thus also the treatment measures is outlined.